The effects of heat on osteoarthritis of the knee - (:unkn) unknown (My University, 2006)
The aim of our study was to evaluate the effects of the manual physical therapy methods conducted by superficial and deep heat treatments of primary bilateral knee osteoarthritis. A randomized, controlled trial was carried out. Eighty patients (160 knees) were included in the analysis. The patients were separated into two groups. Group I (n: 80 knees) performed daily physical therapy programs (ultrasounds, hot packs and exercises) in a period of fifteen days. Group II (n: 80 knees) performed only daily exercise programs in this period. Pain was evaluated by visual analogue scale (VAS) and WOMAC pain scale. Stiffness and functional capacity were measured by WOMAC osteoarthritis index at baseline, at the third and sixteenth weeks. At the third and sixteenth weeks, significant improvement in VAS, WOMAC were observed in both groups, when compared to baseline measures (Group I: p < 0.01, Group II: p < 0.05). At the sixteenth week, more significant improvement was observed in Group 1 than in Group II (p < 0.05). © 2006 VSP.
Keywords: Exercises; Heat; Knee osteoarthritis; Pain; Physical function